2004
DOI: 10.1007/s00040-003-0723-z
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of social parasitism in Acromyrmex leaf-cutting ants: a test of Emery?s rule

Abstract: Summary. Emery's rule predicts that social parasites and their hosts share common ancestry and are therefore likely to be close relatives. Within the leaf-cutting ant genus Acromyrmex, two taxa of social parasites have been found, which are thought to occupy opposite grades of permanent social parasitism, based on their contrasting morphologies: Acromyrmex insinuator differs little in morphology from its freeliving congeneric host species and produces a worker caste, and is thus thought to represent an early g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 34 publications
5
73
0
Order By: Relevance
“…The host-parasite relationships observed for Inquilina, B. falcata and Nasutapis all conform to either the strict or loose form of Emery's rule, and as such, are compatible with previous studies that have suggested social parasites evolved via sympatric speciation (Savolainen and Vepsäläi-nen, 2003;Sumner et al, 2004). However, the host-parasite relationships observed for the Macrogaiea social parasites are not consistent with an intra-specific origin via sympatric speciation.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The host-parasite relationships observed for Inquilina, B. falcata and Nasutapis all conform to either the strict or loose form of Emery's rule, and as such, are compatible with previous studies that have suggested social parasites evolved via sympatric speciation (Savolainen and Vepsäläi-nen, 2003;Sumner et al, 2004). However, the host-parasite relationships observed for the Macrogaiea social parasites are not consistent with an intra-specific origin via sympatric speciation.…”
Section: Discussionsupporting
confidence: 67%
“…The recent research on the phylogenetic relationships of social parasites with their hosts has produced many different results, some seeming to show strong support for sympatric speciation (Savolainen and Vepsäläinen, 2003;Sumner et al, 2004), while others appear to provide evidence against a sympatric origin of social parasites (Carpenter et al, 1993;Choudhary et al, 1994;Ward, 1996;Steiner et al, 2006). It may very well be that the different relationships obtained are due to the different divergence dates of the parasitic species used in each of these studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The individuals used came from the two most abundant patrilines in each colony, with the representation of these patrilines being matched for treatment. Panamanian Acromyrmex octospinosus and A. echinatior are closely related species (Sumner et al 2004b), and workers of A. octospinosus were used for the congeneric treatment. Ants were taken from three laboratory colonies (AoGP, AoAH, and Ao35) that had been collected at the same site in Gamboa, Panama, as that from which the A. echinatior colonies and the M. anisopliae var.…”
Section: Relatedness and Transmissionmentioning
confidence: 99%